PENGARUH FINANCING TO DEPOSITO RATIO, RETURN ON ASSET DAN CAPITAL ADEQUACY RATIO TERHADAP PEMBIAYAAN MURABAHAH PADA BANK MUAMALAT INDONESIA - STIE Lhokseumawe (Sekolah Tinggi Ilmu Ekonomi Lhokseumawe, 2020)
This study aims to examine the effect of Financing to Deposit Ratio, Return on Assets and Capital Adequacy Ratio on Murabahah Financing at Bank Muamalat Indonesia. The data used in this study are 24 secondary data with purposive sampling technique. The method used to analyze the independent variables with the dependent variable is the multiple linear regression method and the classical assumption test. The results of research on Financing to Deposit Ratio and Capital Adequacy variables have a positive and significant effect on Murabahah Financing at Bank Muamalat Indonesia. While Return on Assets has a negative and significant effect on Murabahah Financing at Bank Muamalat Indonesia. The company must determine a higher return level that is beneficial for the company, each company must be able to generate high profits and reduce the obligations that must be issued so as to be able to obtain higher profit.